Corporate Social Responsibility (CSR) communication: Four empirical studies on the German banking industry - Schröder, Philipp (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2023)
This cumulative dissertation presents how commercial banks in Germany communicate their ambitions and commitment regarding corporate responsibility - i.e., CSR. The results of the first article show that the quality of mandatory non-financial reporting needs to be improved and that certain characteristics (e.g., previous reporting experience, reporting format and standard) have a positive influence on reporting quality. The second article shows that the CSR reporting scope on bank websites also has room for improvement and that various banking characteristics such as size, capital market orientation, media visibility or public ownership have an influence on communication. The third article illustrates that credit institutions in Germany are increasingly using social media for CSR communication, but that CSR communication strategies differ (Facebook vs. Twitter). The fourth article discusses CSR communication using advertisements and shows that the conceptual design of advertisements should be in line with the credit institution's business model and is therefore beneficial.

Diese kumulative Dissertation stellt dar, wie Geschäftsbanken in Deutschland ihre Ambitionen und ihr Engagement bzgl. der unternehmerischen Verantwortung - also Corporate Social Responsibility (CSR) - kommunizieren. Die Ergebnisse des ersten Artikels zeigen, dass die Qualität der verpflichtenden nicht-finanziellen Berichterstattung verbesserungswürdig ist und bestimmte Wesensmerkmale (z.B. vorherige Berichtserfahrung, Berichtsformat und -standard) einen positiven Einfluss auf die Berichtsqualität haben. Der zweite Artikel zeigt, dass der CSR-Berichtsumfang auf Bankwebsites ebenfalls ausbaufähig ist und diverse Wesensmerkmale wie Größe, Kapitalmarktorientierung, mediale Sichtbarkeit oder die öffentliche Trägerschaft einen Einfluss auf die Kommunikation haben. Der dritte Artikel verdeutlicht, dass Kreditinstitute in Deutschland vermehrt Soziale Medien für die CSR-Kommunikation verwenden, sich jedoch die CSR-Kommunikationsstrategien unterscheiden (Facebook vs. Twitter). Der vierte Artikel diskutiert CSR-Kommunikation anhand von Werbeanzeigen und zeigt, dass die konzeptionelle Anzeigengestaltung mit dem Geschäftsmodell des Kreditinstituts übereinstimmen sollte und somit vorteilhaft ist.
Corporate Social Responsibility (CSR) Kommunikation: Vier empirische Studien zur deutschen Bankenindustrie
Keywords: 380 Handel, Kommunikation, Verkehr